Health scenario of Karnali Province - Paudel, Tarun; Amgain, K.; Sanjel, S. (Journal of Karnali Academy of Health Sciences, 2018)
Introduction: Although Karnali is an old civilization of Nepal, this province has low human development indexes and the indicators of health are low. This study was carried out to comprehend the trend of public health indicators and disease pattern of Karnali Province. Methods: Descriptive study using provincial three years’ health data were reviewed from all the 10 districts of Karnali Province using per forma. Data entered in Microsoft Excel software were transferred into the statistical package for social sciences version 21 and descriptive analysis was carried out. Results: Previous three years’ data were analyzed. The last years’ results were BCG coverage was 106.0%, DPT/Hepa B was 93.0%, 95.0%, tetanus toxoid (TT) 2 & tetanus toxoid 2+ was 82.0%, 0-11 months’ growth monitoring was 126.0%, 0-23 months’ underweight children was 8.0%, pneumonia among new acute respiratory infection was 24.0% prevalence of acute respiratory infection was 949/1,000, prevalence of diarrhea was 709/1,000 and severe dehydration among diarrhea was 0.9%. Four Antenatal chick up was 55.0% institutional delivery was 67.0%, delivery by skill birth attendant was 56.0%, health examination within 24 hours of delivery was 65.0%, and contraceptive prevalence (CPR) rate was 35.0%. Likewise, treatment success rate of tuberculosis was 86.0%, new case detection for rate/100,000 tuberculosis was 0.5, HIV Incidence rate/10,000 was 5.3 and outpatient department attendance was 83.0%. Among top 10 diseases, respiratory infection was the first with 14.8%, followed by acute peptic disorders 10.4%, headache 7.9%, worm infestations 7.2% and fall injuries/ fractures found 5.9%. Conclusions: The indicators of health condition of Karnali Province are markedly low in comparison to the other provinces as well as the national figure. The utilization of public health services has to be reinforced in the province and districts.